Epic negation : the dialectical poetics of late modernism - Blanton, C. D. (Charles Daniel), 1968- (New York : Oxford University Press, 2015)
"Epic Negation examines the dialectical turn of modernist poetry over the interwar period, arguing that late modernism inverts the method of Ezra Pound's "poem including history" to conceive a negated mode of epic, predicated on the encryption of disarticulated historical content. Compelled to register the force of a totality it cannot represent, this negated epic reorients the function of poetic language and reference, remaking the poem, and late modernism generally, as a critical instrument of dialectical reason. Part I reads The Waste Land alongside the review it prefaced, The Criterion, arguing that the poem establishes the editorial method with which T.S. Eliot constructs the review's totalizing account of culture. Dividing the epic's critical function from its style, Eliot not only includes history differently, but also formulates an intricately dialectical account of the interwar crisis of bourgeois culture, formed in the image of a Marxian critique it opposes. Part II turns to the second war's onset, tracing the dislocated formal effects of an epic gone underground. In the elegies and pastorals of W.H. Auden and Louis MacNeice, lyric forms divulge the determining force of unmentionable but universal events, dividing experience against consciousness. With H.D.'s war trilogy, produced in a terse exchange with Freud's Moses, even the poetic image lapses, associating epic with the silent historical force of the unconscious as such"--
Part 1: Including history. 1. The dialectical poetics of late modernism. Dialectical poetics ; Negated epics ; The dialectics of late modernism ; 2. An organ of documentation : Eliot and order. Notes on order and method ; Eliot's nomology ; Allusion and reference : against the mythic method ; O swallow swallow ; Eliot's indication : The waste land as method ; And down we went : The waste land as epic ; 3. Date line : including history. A literary program ; Including history ; Date line(s) ; Two epics ; 4. Eliotic marxism : notes toward a dialectic of culture. Last words ; Another date line ; Toward definition : Eliotic epistemology ; An absolute criterion : Eliotic praxis ; Eliotic marxism : culture as praxis ; Negation : epic as critique -- Part 2: Including negation. 5. A poem is not poetry. War poetry ; Seriality ; Silence ; 6. Auden's monadology. Killing Ernst Toller ; Including history occasionally ; Monadology : the end of lyric ; Elegy and daybook : two allusions ; Goliath ; Ways of happening ; 7. MacNeice's dying fall. Enforming : poetry's ends ; September 1, 1939, again ; Pastoral and epic: the orchestra and the bonfire ; Air wars ; Dying fall : epic as elegy ; 8. H.D.'s incidents. Freud and words ; The hieroglyph of the unconscious ; Mosaic visions and revisions ; Pararhyme and afterimage ; Angles of incidence : experiencing totality ; Cryptonymy : two universals.
Vendor-supplied metadata.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: American poetry -- 20th century -- History and criticism -- Theory, etc; English poetry -- 20th century -- History and criticism -- Theory, etc; Modernism (Literature); Poetry -- Explication; Epic poetry, American -- History and criticism; Epic poetry, English -- History and criticism; Poetry, Modern -- 20th century -- History and criticism; Poetics; Literature -- Philosophy; Poésie américaine -- 20e siècle -- Histoire et critique -- Théorie, etc; Poésie anglaise -- 20e siècle -- Histoire et critique -- Théorie, etc; Modernisme (Littérature); Poésie -- Explication de texte; Poésie épique américaine -- Histoire et critique; Poésie épique anglaise -- Histoire et critique; Poétique.; LITERARY CRITICISM -- Poetry; Literature -- Philosophy; Epic poetry, American; Epic poetry, English; Modernism (Literature); Poetics; Poetry -- Explication; Poetry, Modern; 1900-1999; Electronic books; Criticism, interpretation, etc